Magnetic resonance-guided focused ultrasound surgery treatment of non-spinal intra-articular osteoblastoma: feasibility, safety, and outcomes in a single-center retrospective analysis. (1st January 2019) - Arrigoni, Francesco; Bruno, Federico; Palumbo, Pierpaolo; Zugaro, Luigi; Zoccali, Carmine; Barile, Antonio; Masciocchi, Carlo
Abstract: Background: Interventional radiology, thanks to its low invasiveness and possibility to reduce the average time for the patients to come back to their normal activity, is becoming more and more promising and diffused in multiple fields. Employed without needles, MRgFUS is probably the less invasive techniques among the ones belonging to the field of interventional radiology. Purpose: To evaluate safety and effectiveness of MRgFUS in the treatment of a rare and benign, though disabling, bone lesion: intra-articular osteoblastoma. Materials and methods: A retrospective study was carried out on 6 patients (mean, 21 years) treated in the last 2 years with MRgFUS for symptomatic, histologically proved intra-articular osteoblastoma. The main inclusion criterion was the presence of a good acoustic window. The procedures consisted in MR-guided ablation, using high intensity ultrasound beams focused on the target lesion. Spinal anesthesia or peripheral nerve block was used. Clinical (based on pain and functional scales) and imaging follow-up studies were performed up to 1 year after treatment. Complications were recorded. Multiple linear regression and analysis of variance were used to assess correlations. Results: All the procedures were technically successful; no complications were observed. Painful symptomatology decreased of 88% at 6 months and 98% at 12 months ( p < 0.0001), and was associated to functional improvement ( p = 0.002). MRI and CT controls showed disappearance of all signs of disease and bone inflammation with a marked tendency to bone healing. Conclusion: This study shows the safety and effectiveness of MRgFUS in the treatment of intra-articular osteoblastoma with a good acoustic window.